The structure of cell adhesion molecule uvomorulin. Insights into the molecular mechanism of Ca2+-dependent cell adhesion. - Ringwald, M (1987)
We have determined the amino acid sequence of the Ca2+-dependent cell adhesion molecule uvomorulin as it appears on the cell surface. The extracellular part of the molecule exhibits three internally repeated domains of 112 residues which are most likely generated by gene duplication. Each of the repeated domains contains two highly conserved units which could represent putative Ca2+-binding sites. Secondary structure predictions suggest that the putative Ca2+-binding units are located in external loops at the surface of the protein. The protein sequence exhibits a single membrane-spanning region and a cytoplasmic domain. Sequence comparison reveals extensive homology to the chicken L-CAM. Both uvomorulin and L-CAM are identical in 65% of their entire amino acid sequence suggesting a common origin for both CAMs.